STRATEGI PROMOSI KLINIK TERAPI ZONA MELALUI PROMOTION MIX UNTUK MEMBANGUN BRAND VALUE DAN LOYALITAS PELANGGAN KESEHATAN TRADISIONAL (STUDI KASUS PADA KLINIK TERAPI ZONA CABANG LEBAK BULUS JAKARTA SELATAN) - Aziz, Abdul (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of this research is to find out the promotion strategy of Zone Therapy Clinic through promotion mix to build brand value and loyalty of traditional health customers. This study uses marketing theory, Marketing Mix Theory, Marketing Mix Communication Theory and SWOT Analysis. This research method uses a qualitative approach with a case study research method. The results of this research are the Zone Therapy Clinic using marketing communication strategies using Advertising activities, Direct Marketing and then Word of Mount (word of mouth marketing) with the Segmentation, Tactics and Value approach. In building brand value and customer loyalty, the Zone Therapy Clinic always makes an innovation to improve both its marketing strategy both online and offline, by creating the latest content and design for marketing needs to be easily accepted by the public both with advertising, direct marketing and marketing patterns by word of mouth or word if mounted by first determining the segmentation, tactics and values ​​that will be given later. In addition, in terms of service, which is trying as much as possible to provide the best by aligning themselves with its consumers then asking more questions, greeting and providing education in accordance with the needs of its customers.